Pengaruh Bimbingan Kelompok dengan Teknik Diskusi dalam Meningkatkan Konsep Diri Positif Siswa - Weli Marista; M Ferdiansyah; Nurlela Nurlela (Syifaul Qulub: Jurnal Bimbingan dan Konseling Islam, 2021)
Self-concept is an individual's understanding of himself physically and psychologically including the advantages and disadvantages he has. This study aims to determine the effectiveness of group guidance services using discussion techniques to improve students' positive self-concepts. This study uses a quantitative approach and the method used in this study is a pre-experimental design study with one group pretest and posttest design. This research was conducted at SMK Muhammadiyah 2 Palembang, and the samples of this research were students of class XII AKL 2 which amounted to 32 students after being given a pretest taken as many as 8 students who had a low positive self-concept. Sampling using a random sample technique. The results of the study were tested with the Wilcoxon Signed Rank Test statistic which was used to measure the significance of the difference between 2 groups in paired data on an ordinal or interval scale but with a non-normal data distribution. Based on the table of results of the Wilcoxon Signed Rank Test analysis, it can be seen that the Asymp probability number. Sig. (2-tailed) students' academic procrastination in doing assignments is 0.012, or the probability is below alpha 0.05 (0.012≤0.05). From the results obtained, Ho is rejected and Ha is accepted. Thus, it shows that group guidance with discussion techniques is effective in increasing students' positive self-concept.